What a Woman Ought to Be and to Do : Black Professional Women Workers during the Jim Crow Era. - Shaw, Stephanie J. (Women in culture and society., 1996)
Stephanie J. Shaw takes us into the inner world of American black professional women during the Jim Crow era. This is a story of struggle and empowerment, of the strength of a group of women who worked against daunting odds to improve the world for themselves and their people. Shaw's remarkable research into the lives of social workers, librarians, nurses, and teachers from the 1870s through the 1950s allows us to hear these women's voices for the first time. The women tell us, in their own words, about their families, their values, their expectations. We learn of the forces and factors that m.